COMPARISON STUDY OF DOMESTIC AND FOREIGN TOURISTS’ PERSPECTIVE: THE STANDARDS AND PRODUCT VALUES OF HALAL TOURISM - G R Nurazizah; F Rahmafitria (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2021)
Each country that developed halal tourism destinations, had arranged halal standards differently, for instance Indonesia which arranges the standards based on Islamic sharia values in the context of tourism facilities, services and management. However, due to tourism activities are related to recreational motivation, such as seeking pleasure and relaxation, the halal tourism standards that expected by tourists need to be continuously studied. Because the target of tourists is not only domestic, the perception of foreign Muslim tourists should be used as a comparison, including analysing their preferences. This study is very useful for the next development of halal tourism in Indonesia. The purpose of this study is to compare and examine the relationship between preferences and perceptions of halal tourism and intention to stay at halal hotels. A total of 45 foreign Muslim tourists and 200 domestic Muslim tourists were used as respondents to analyse their preferences for halal tourism quantitatively. The analysis shows the significant differences between the preferences of both tourism groups in terms of the importance of halal standard and the perceived value they felt. Furthermore, the result of analysis shows that there is an associative relationship between preferences and perceptions toward intention to stay at Halal Hotels.